The Effectiveness of 'Talid Platform' for Developing Knowledge of Saudi Cultural Heritage for the 1st Grade of Intermediate School (The International Journal of Educational Sciences and Arts, 2024)
This study aimed to determine the effectiveness of Talid platform in developing knowledge of Saudi cultural heritage for male and female 1st grade intermediate school students. The one-group quasi-experimental approach was used by applying the pre- and post-test, and the study tool was an electronic questionnaire consisting of 20 closed questions and divided into four axes (antiquities - intangible heritage - urban heritage - handicrafts).The research was applied to a sample of (30) male and female 1st grade of intermediate students, and the results showed that there were statistically significant differences between the average scores of the study sample in the pre- and post-measurement in favor of the post-measurement in the three axes (antiquities - intangible heritage - urban heritage). The results also demonstrated the effectiveness of using interactive multimedia as a means of developing knowledge of Saudi cultural heritage for middle school students, both male and female.
Keywords: Cultural Heritage; Website; Interactive Multimedia; Antiquities; Intangible Heritage; Urban Heritage; Handicrafts